Preparation method and application of LiF-rich nanofiber interface layer on surface of copper current collector

By using a nanofiber interface layer rich in LiF on the copper current collector surface in lithium metal batteries, the problems of uneven deposition/peeling behavior and unsuitable SEI layer structure are solved, and the uniform diffusion of lithium ions and improved battery cycle stability are achieved.

CN119905597APending Publication Date: 2025-04-29QINGDAO UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510117822.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Existing lithium metal batteries have challenges in the uneven lithium ion deposition/peeling behavior, unsuitable SEI layer structure composition, and electrode volume expansion/contraction, affecting their energy density and safety.

Method used

Using the preparation method of the nanofiber interface layer rich in LiF on the copper current collector, an interface layer with a three-dimensional nanofiber network structure was prepared by electrospinning and heat treatment processes, which increased the surface energy of the SEI film and reduced the Li+ diffusion energy barrier.

Benefits of technology

The uniform diffusion and distribution of lithium ions are achieved, uniform lateral deposition of lithium is promoted, the Coulomb efficiency and long-term cycle stability of battery circulation are improved, and the stability of the electrode/electrolyte interface is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905597A_ABST
    Figure CN119905597A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a LiF-rich nanofiber interface layer on the surface of a copper current collector, and the preparation method comprises the following steps: adding a lithium salt into a solvent, uniformly mixing, adding a polymer matrix material, and uniformly mixing to obtain a spinning precursor solution; performing electrostatic spinning on the spinning precursor solution to obtain a nanofiber membrane; drying the nanofiber membrane to obtain a nanofiber layer; the nanofiber layer is subjected to heat treatment and then cooled to the room temperature, and the nanofiber interface layer rich in LiF is obtained. The nanofiber interface layer has a three-dimensional nanofiber network structure, can buffer huge volume change in the cycle period of the battery, and improves the stability of an electrode / electrolyte interface; the polymer matrix has a high specific surface area and mutually communicated pore structures, so that a convenient ion / electron transmission channel can be provided, and uniform lithium ion flux is realized; liF can improve the surface energy of an SEI film and reduce Li < + > diffusion energy barriers, so that lithium ions are quickly and uniformly diffused and uniformly distributed in the electrolyte, and uniform and transverse deposition of lithium is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and particularly relates to a preparation method and application of a nanofiber interface layer rich in LiF on the surface of a copper current collector. Background Art

[0002] With the popularity of new energy vehicles, people's demand for battery safety and high energy density is growing. Metallic lithium is considered to be an ideal negative electrode material for high-energy-density batteries due to its ultra-high theoretical specific capacity (3860 mAh / g) and extremely low redox potential (−3.040 V vs standard hydrogen electrode). Therefore, lithium metal batteries using metallic lithium as negative electrodes are expected to break through the energy density bottleneck of lithium-ion batteries at this stage and significantly improve the battery life in application scenarios such as mobile electronic terminals and electric vehicles. However, the inherent high reactivity of lithium metal causes it to spontaneously react with any non-aqueous electrolyte to form an ion-conducting and electronically insulating solid electrolyte interface (SEI) film when it comes into contact with any non-aqueous electrolyte. In order for lithium metal batteries to truly approach or meet the requirements of high energy density and high safety in the commercial field, the following problems still need to be solved: (1) How to improve the uneven deposition / stripping behavior of lithium ions on the electrode surface to regulate the lithium deposition morphology and thus avoid the formation and growth of lithium dendrites; (2) How to adjust the structural composition of the SEI layer generated on the electrode surface to enhance its affinity for lithium metal, thereby achieving uniform lithium nucleation and growth behavior; (4) How to suppress the volume expansion / contraction of the electrode during the cycle and further promote the controllable construction of a uniform and stable SEI layer on the electrode surface. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a preparation method and application of a nanofiber interface layer rich in LiF on the surface of a copper current collector, so as to improve the uneven deposition / stripping behavior of lithium ions on the electrode surface, regulate the structural composition of the SEI layer, etc. LiF functional particles can increase the surface energy of the SEI film and reduce the Li + The diffusion energy barrier enables lithium ions to diffuse and distribute quickly and evenly in the electrolyte, promotes uniform lateral deposition of lithium, and improves the coulombic efficiency of the battery cycle and long-term cycle stability.

[0004] To this end, the present invention provides a method for preparing a nanofiber interface layer rich in LiF on the surface of a copper current collector, comprising: (1) adding lithium salt to a solvent and stirring and mixing uniformly, and then adding a polymer matrix material and stirring and mixing uniformly to obtain a spinning precursor solution; (2) electrospinning the spinning precursor solution to obtain a nanofiber membrane; and drying the nanofiber membrane by air blast drying and vacuum drying to obtain a nanofiber layer; (3) The nanofiber layer is heat treated and then cooled to room temperature to obtain a LiF-rich nanofiber interface layer.

[0005] Preferably, in step (1), the lithium salt comprises at least one of lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), lithium difluorooxalatoborate, lithium hexafluoroarsenate, and lithium hexafluorophosphate; and the mass ratio of the lithium salt to the polymer matrix material is (1-4):(7-20).

[0006] Preferably, in step (1), the polymer matrix material includes at least one of polyacrylonitrile, polyvinylidene fluoride, polyethylene oxide and polydimethylsiloxane.

[0007] Preferably, in step (1), the polymer matrix material comprises polyacrylonitrile and polyvinylidene fluoride, and the mass ratio of polyacrylonitrile to polyvinylidene fluoride is (1-3): (0.5-1.5).

[0008] Preferably, in step (1), the solvent is N, N-dimethylformamide, and the mass ratio of the lithium salt to the volume of the solvent is (0.1-0.4) g: (10-20) mL.

[0009] Preferably, the step (2), the electrospinning method comprises: wrapping the receiving roller of the electrospinning machine with copper foil, taking the spinning precursor solution into the needle tube and connecting the needle, and adjusting the distance between the needle and the receiving roller to 10-15 cm; spinning for 8-15 h under the conditions of the needle tube advancement rate of 0.02-0.05 mm / min and the spinning voltage of 20-35 kV, to prepare a fiber membrane with a thickness of 20-30 μm and a width of 80-120 mm.

[0010] Preferably, in step (2), the forced air drying temperature is 50-80°C and the time is 5-8h; the vacuum drying temperature is 50-80°C and the time is 20-28h.

[0011] Preferably, in step (3), the heat treatment method comprises: placing the nanofiber layer in a Fresnel furnace, heating the temperature to 200-300°C at a heating rate of 1-3°C / min, heat treating for 1-3 h, and then naturally cooling to room temperature.

[0012] The present invention also provides application of the prepared LiF-rich nanofiber interface layer in a battery.

[0013] Compared with the prior art, the advantages and positive effects of the present invention are as follows: the present invention provides a preparation method and application of a nanofiber interface layer rich in LiF on the surface of a copper current collector. The present application combines organic polymers and inorganic functional particles together through an electrospinning process. The prepared nanofiber interface layer has a three-dimensional nanofiber network structure, which can serve as a host for lithium deposition, can buffer the huge volume change during battery cycling, and improve the stability of the electrode / electrolyte interface; the polymer matrix has a high specific surface area and an interconnected pore structure, which can provide a convenient ion / electron transmission channel, balance the charge distribution on the surface of the lithium negative electrode during charging and discharging, and achieve uniform lithium ion flux; the LiF functional particles can increase the surface energy of the SEI film and reduce the Li + The diffusion energy barrier allows lithium ions to diffuse and distribute rapidly and evenly in the electrolyte, promoting uniform lateral deposition of lithium, thereby synergistically regulating highly reversible lithium deposition / stripping behavior. In addition, the mechanical properties and flexibility of the nanofiber interface layer can also be enhanced to resist the destruction of lithium dendrites. In addition, the nanofiber interface layer of the present application can also promote the uniform deposition of lithium ions and reduce the growth of lithium dendrites.

[0014] After reading the specific embodiments of the present invention in conjunction with the accompanying drawings, other features and advantages of the present invention will become more clear. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is the SEM image of the LiBF4@PVDF-PAN nanofiber membrane of Example 1 of the present invention; Figure 2 This is a SEM image of the LiF@F-OPAN nanofiber membrane of Example 1 of the present invention; Figure 3 FTIR spectra of PVDF-PAN nanofiber membrane and F-OPAN nanofiber membrane of Example 2 of the present invention; Figure 4 Surface SEM images and cross-sectional SEM images of blank copper foil (Bare Cu) at different lithium deposition capacities; Figure 5 Surface SEM images and cross-sectional SEM images of LiF@F-OPAN nanofiber membranes at different lithium deposition capacities; Figure 6 This is one of the cycle performance test graphs of the lithium-copper battery of Example 3, Comparative Example 1, and Comparative Example 2 at different current densities and different lithium deposition capacities; Figure 7 The second graph is a cycle performance test graph of the lithium-copper battery of Example 3, Comparative Example 1 and Comparative Example 2 at different current densities and different lithium deposition capacities; Figure 8 The lithium copper battery of Example 3 at 1 mA cm-2 and 1 mAh cm -2 The charge and discharge curves of different cycle numbers under the conditions of ; Fig. 9 This is a test diagram of the cycle performance of the lithium-poor negative electrode battery of Example 4 at a charging rate of 0.5C. DETAILED DESCRIPTION

[0016] The present invention will be further described below in conjunction with specific embodiments. These embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. Meanwhile, after reading the present invention, those skilled in the art may make various modifications or changes to the present invention, and these equivalent forms also fall within the scope limited by the appended claims of the application.

[0017] The method for preparing a nanofiber interface layer rich in LiF on the surface of a copper current collector of the present invention comprises: (1) adding lithium salt to a solvent and stirring and mixing uniformly, and then adding a polymer matrix material and stirring and mixing uniformly to obtain a spinning precursor solution; The lithium salt includes at least one of lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), lithium difluorooxalatoborate, lithium hexafluoroarsenate, and lithium hexafluorophosphate.

[0018] The mass ratio of lithium salt to polymer matrix material is (1-4):(7-20).

[0019] The polymer matrix material may include at least one of polyacrylonitrile, polyvinylidene fluoride, polyethylene oxide, and polydimethylsiloxane.

[0020] In this embodiment, the polymer matrix material includes polyacrylonitrile and polyvinylidene fluoride, and the mass ratio of polyacrylonitrile to polyvinylidene fluoride is (1-3): (0.5-1.5).

[0021] Preferably, the mass ratio of lithium salt to polymer matrix material is (2-4): (12-17), and the mass ratio of polyacrylonitrile to polyvinylidene fluoride is (1.5-2.5): (0.7-1.2); the LiF-rich nanofiber interface layer can have a three-dimensional nanofiber network structure, which can serve as a host for lithium deposition, buffer the huge volume change during battery cycling, and improve the stability of the electrode / electrolyte interface; the polymer matrix has a high specific surface area and an interconnected pore structure, which can provide a convenient ion / electron transmission channel, balance the charge distribution on the surface of the lithium negative electrode during charging and discharging, and achieve uniform lithium ion flux; the LiF functional particles can increase the surface energy of the SEI film and reduce the Li +The diffusion energy barrier allows lithium ions to diffuse and distribute rapidly and evenly in the electrolyte, promoting uniform lateral deposition of lithium, thereby synergistically regulating highly reversible lithium deposition / stripping behavior. In addition, the mechanical properties and flexibility of the lithium-philic nanofiber interface layer on the surface of the copper current collector can also be enhanced to resist the destruction of lithium dendrites. In addition, the lithium-philic nanofiber interface layer on the surface of the copper current collector of the present application can also promote the uniform deposition of lithium ions and reduce the growth of lithium dendrites.

[0022] The solvent is N, N-dimethylformamide, and the mass ratio of the lithium salt to the volume ratio of the solvent is (0.1-0.4) g: (10-20) mL. Preferably, the mass ratio of the lithium salt to the volume ratio of the solvent is (0.25-0.35) g: (12-17) mL. The lithium salt and the polymer matrix material can be mixed evenly, so that the spinning precursor liquid reaches a suitable viscosity, which is beneficial to the spinning of nanofibers, and the nanofibers can be evenly spun and there are no obvious droplets on the nanofiber membrane.

[0023] (2) electrospinning the spinning precursor solution to obtain a fiber membrane; and drying the fiber membrane by air blowing and vacuum drying to obtain a nanofiber membrane; The electrostatic spinning method comprises: wrapping a receiving roller of an electrostatic spinning machine with copper foil, taking a spinning precursor solution into a needle tube and connecting a needle, adjusting the distance between the needle tube and the receiving roller to 10-15 cm; spinning for 8-15 h under the conditions of a needle tube advancement rate of 0.02-0.05 mm / min and a spinning voltage of 20-35 kV, and preparing a nanofiber membrane with a thickness of 20-30 μm and a width of 80-120 mm. The electrostatic spinning method of the present invention can be beneficial to the spinning of nanofibers, and can make the nanofibers uniform and without obvious droplets on the nanofiber membrane.

[0024] The blast drying temperature is 50-80°C and the time is 5-8h; the vacuum drying temperature is 50-80°C and the time is 20-28h. The organic solvent N,N-dimethylformamide DMF in the fiber membrane can be volatilized by blast drying and vacuum drying.

[0025] (3) The nanofiber membrane is heat treated and then cooled to room temperature to obtain a LiF-rich nanofiber interface layer.

[0026] The heat treatment method includes: placing the nanofiber membrane in a Fresnel furnace, heating the temperature to 200-300°C at a heating rate of 1-3°C / min, and naturally cooling the nanofiber membrane to room temperature after heat treatment for 1-3 hours.

[0027] Preferably, the heat treatment temperature is 260-300° C. and the heat treatment time is 2-3 h.

[0028] The LiF-rich nanofiber interface layer prepared by the present invention can be used to prepare batteries. Specifically, the composite copper current collector loaded with the LiF-rich nanofiber interface layer can be used as the negative electrode of the battery. The battery prepared by the LiF-rich nanofiber interface layer of the present invention has excellent electrochemical stability and cycle performance.

[0029] The advantages and positive effects of this application include: (1) Preparation of LiF-rich nanofiber-based artificial SEI layer on copper foil surface: This application uses electrospinning and heat treatment processes to effectively construct a LiF@F-OPAN nanofiber layer on the copper foil surface to prepare an artificial SEI layer. PVDF can be melted by heat treatment. The molten PVDF can be used as a pore size regulator or a physical linker to accelerate the Li + The transmission of copper foil and nanofiber layer can achieve close bonding, effectively enhancing the interface stability and compatibility between the two, which is conducive to the long-term stable cycle of the battery.

[0030] (2) Regulation of lithium deposition / stripping behavior: Through heat treatment, polyacrylonitrile PAN can be converted into oxidized polyacrylonitrile OPAN rich in polar groups; oxidized polyacrylonitrile OPAN has excellent Li + affinity, which can make the Li + Flux homogenization helps to achieve uniform lithium deposition and avoid the growth of lithium dendrites.

[0031] Through the heat treatment process, LiBF4 can be transformed into beneficial LiF particles in situ. LiF functional particles can increase the surface energy of SEI film and reduce Li + The diffusion energy barrier allows lithium ions to diffuse and distribute rapidly and evenly in the electrolyte, promoting uniform lateral deposition of lithium, thereby synergistically regulating highly reversible lithium deposition / stripping behavior and improving the coulombic efficiency and long-term cycle stability of the battery cycle. On this basis, the three-dimensional nanofiber network is used as a flexible support for the SEI film to buffer the volume deformation of the electrode during battery cycling and enhance the interface stability, while guiding lithium to deposit evenly from bottom to top and forming a stable interface layer rich in LiF, thereby promoting the improvement of the electrochemical reversibility and stability of the lithium negative electrode.

[0032] (3) Regulation of SEI membrane structure and composition: Using a three-dimensional nanofiber network as a flexible support for the SEI membrane and guiding the in-situ generation of the SEI membrane in the small gaps between the fibers, the volume deformation of the electrode is effectively suppressed, giving the SEI layer good structural stability and flexibility, thereby preventing the SEI membrane from breaking as the volume of metallic lithium changes. Benefiting from the co-modification of LiF and PVDF, a stable and strong LiF-rich interface layer is constructed in situ, which greatly promotes interfacial charge transfer, reduces parasitic reactions, and consolidates the electrode / electrolyte interface, which can be conducive to the rapid development of high-energy-density and high-safety lithium-free negative electrode batteries. Example 1

[0033] The method for preparing the LiF-rich nanofiber interface layer on the surface of the copper current collector of this embodiment comprises the following steps: (1) Preparation of spinning precursor solution: Weigh 0.45 g of lithium tetrafluoroborate (LiBF4), add it to 15 mL of N, N-dimethylformamide (DMF), stir and ultrasonicate the solution for 5 min. After the solution is mixed evenly, add 1 g of polyacrylonitrile (PAN) and 0.5 g of polyvinylidene fluoride (PVDF) to the above solution, stir in a constant temperature water bath at 60°C for 2 h until PAN and PVDF are completely dissolved, and obtain a spinning precursor solution.

[0034] (2) Preparation of nanofiber membrane by electrospinning: Cut a 32 cm × 25 cm copper foil to wrap the receiving roller of the electrospinning machine, take 3 mL of the above spinning precursor solution into the needle tube, connect the needle with a diameter of 800 μm, and adjust the receiving distance to 12 cm. Spin for 10 h at a needle tube propulsion rate of 0.025 mm / min and a spinning voltage of 26 kV to prepare a nanofiber membrane with a thickness of 20-30 μm and a width of 90 mm. After air drying (60°C air blowing for 6 h) and vacuum drying (60°C vacuum drying for 24 h), LiBF4@PVDF-PAN nanofiber membrane was obtained.

[0035] (3) Heat treatment A 10 cm×15 cm LiBF4@PVDF-PAN nanofiber membrane was placed in a muffle furnace and heated to 260 °C at a heating rate of 2 °C / min. After heat treatment at 260 °C for 2 h, it was naturally cooled to room temperature to obtain a LiF-rich nanofiber interface layer, which was recorded as LiF@F-OPAN nanofiber membrane. Example 2

[0036] The method for preparing the LiF-rich nanofiber interface layer on the surface of the copper current collector of this embodiment comprises the following steps: (1) Preparation of spinning precursor solution: 1 g of polyacrylonitrile (PAN) and 0.5 g of polyvinylidene fluoride (PVDF) were mixed and stirred in a constant temperature water bath at 60°C for 2 h until PAN and PVDF were completely dissolved to obtain a spinning precursor solution.

[0037] (2) Preparation of nanofiber membrane by electrospinning: Cut a copper foil of 32 cm × 25 cm size to wrap the receiving roller of the electrospinning machine, take 3 mL of the above spinning precursor solution into the needle tube, connect the needle with a diameter of 800 μm, and adjust the receiving distance to 12 cm. Spin for 10 h under the conditions of needle tube advancement rate of 0.025 mm / min and spinning voltage of 26 kV to prepare a nanofiber membrane with a thickness of 20-30 μm and a width of 90 mm. After air drying (60℃ air blowing for 6h) and vacuum drying (60℃ vacuum drying for 24h), F-PAN nanofiber membrane was obtained.

[0038] (3) Heat treatment A 10 cm × 15 cm PVDF-PAN nanofiber membrane was placed in a muffle furnace and heated to 260 °C at a heating rate of 2 °C / min. After heat treatment at 260 °C for 2 h, it was naturally cooled to room temperature to obtain a LiF-rich nanofiber interface layer, which was recorded as F-OPAN nanofiber membrane.

[0039] Figure 1 This is a SEM image of the LiBF4@PVDF-PAN nanofiber membrane of Example 1 of the present invention. The LiBF4@PVDF-PAN nanofibers are evenly distributed and there are no droplets on the fiber membrane.

[0040] Figure 2 This is a SEM image of the LiF@F-OPAN nanofiber membrane of Example 1 of the present invention. Since the heat treatment temperature is higher than the melting point of PVDF, PVDF will be in a molten state, and thus the nanofibers will be in a partially molten state.

[0041] Figure 3 The FTIR spectra of the F-PAN nanofiber membrane and the F-OPAN nanofiber membrane of Example 2 of the present invention are shown in Figure 2. By comparing the infrared spectra before and after heat treatment, it can be seen that the infrared spectrum at 2245 cm −1 The peak band of C≡N decreases sharply and is located at 1580-1650cm −1 The C=O and C=N peaks at 2940 cm-1 increase sharply. −1 The number of nearby C-H bonds decreased, indicating that PAN underwent cyclization and partial oxidation after heat treatment.

[0042] Figure 4 Surface SEM images and cross-sectional SEM images of blank copper foil (Bare Cu) at different lithium deposition capacities; Figure 5The surface SEM images and cross-sectional SEM images of LiF@F-OPAN nanofiber membranes at different lithium deposition capacities; after different capacities of lithium deposition, the fiber morphology of the nanofiber layer is still visible, and lithium is preferentially deposited under the nanofiber layer. As the lithium deposition capacity increases, the thickness of the lithium deposition layer also increases. Compared with Bare Cu and F-PAN, the lithium deposition layer of LiF@F-OPAN is thinner and the lithium distribution is more uniform. In order to further observe the morphology of lithium deposition under the nanofiber layer, part of the surface nanofiber layer is removed after lithium deposition. Bare Cu presents an uneven lithium deposition morphology. In contrast, the LiF@F-OPAN nanofiber layer presents a uniform, dendrite-free, spherical lithium deposition morphology and a more uniform and smooth deposition surface. Example 3

[0043] The battery of this embodiment is a lithium copper battery, and the positive electrode of the lithium copper battery is a lithium sheet.

[0044] The composite copper foil loaded with LiF@F-OPAN nanofiber membrane of Example 1 was cut into 10 mm diameter discs as the negative electrode, a lithium sheet as the positive electrode, a polyethylene film with a diameter of 19 mm as the separator, and 90 μL of ether electrolyte to assemble the battery. The ether electrolyte includes 1.0 M lithium bistrifluoromethanesulfonyl imide (LiTFSI), 2 wt.% lithium nitrate (LiNO3) and a solvent, and the solvent includes 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) in a volume ratio of 1:1. Example 4

[0045] The battery of this embodiment is a lithium-poor negative electrode battery. The lithium copper battery of Example 3 was charged at 0.5 mA cm -2 Lithium was deposited for 1 h at a current density of , the battery was disassembled, the copper foil was taken out, and the side of the copper foil on which lithium was deposited was used as the negative electrode; the positive electrode included LiFePO4, and a lithium-poor negative electrode battery was assembled using a PE separator with a diameter of 16.5 mm and adding 40 μL of ether electrolyte.

[0046] Lithium iron phosphate (LiFePO4): conductive carbon black (Super P): PVDF was mixed in a mass ratio of 8:1:1, and N-methylpyrrolidone (NMP) was used as a solvent. The positive electrode slurry was prepared by grinding, and then the slurry was evenly scraped on the carbon-coated aluminum foil with a scraper. The coating thickness was 180μm, and after air drying (60℃ air blowing for 6h) and vacuum drying (60℃ vacuum drying for 24h), it was cut into a 10 mm diameter disc as the positive electrode. The ether electrolyte includes 1.0 M lithium bistrifluoromethanesulfonyl imide (LiTFSI), 2wt.% lithium nitrate (LiNO3) and a solvent, and the solvent includes 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME) in a volume ratio of 1:1.

[0047] Comparative Example 1 The lithium-copper battery of this comparative example 1 is substantially the same as the lithium-copper battery of Example 3, except that the negative electrode of the lithium-copper battery of this comparative example 1 is copper foil.

[0048] Comparative Example 2 The lithium copper battery of this comparative example 2 is substantially the same as the lithium copper battery of Example 3, except that the negative electrode of the lithium copper battery of this comparative example 2 is the F-PAN nanofiber membrane of Example 2.

[0049] Figure 6 This is one of the cycle performance test graphs of the lithium-copper battery of Example 3, Comparative Example 1, and Comparative Example 2 at different current densities and different lithium deposition capacities; Figure 7 The second test graph of the cycle performance of the lithium copper battery of Example 3, Comparative Example 1 and Comparative Example 2 at different current densities and different lithium deposition capacities; at different current densities and different lithium deposition capacities, the cycle stability of LiF@F-OPAN is better than that of F-OPAN and Bare Cu. When the current density is 1 mA cm -2 , the deposition capacity of lithium is 1 mAh cm -2 When LiF@F-OPAN is charged, it can maintain 260 stable cycles and the Coulombic efficiency remains above 98%.

[0050] Figure 8 The lithium copper battery of Example 3 at 1 mA cm -2 and 1 mAh cm -2 The charge and discharge curves of different cycle numbers under the conditions of ; the polarization voltage of LiF@F-OPAN did not increase significantly after 250 cycles, and the charge and discharge curves under different cycle numbers almost overlapped, showing good reversibility during the lithium deposition / stripping process.

[0051] Fig. 9 This is a test diagram of the cycle performance of the lithium-poor negative electrode battery of Example 4 at a charging rate of 0.5C. Under the condition of a charge and discharge rate of 0.5C, the capacity retention rate of the lithium-poor negative electrode battery loaded with LiF@F-OPAN N / P=1.5 can reach 87.5% after 100 cycles, and the average coulomb efficiency can reach 99.87%.

[0052] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for a person skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to replace some of the technical features therein by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions claimed to be protected by the present invention.

Claims

1. A method for preparing a nanofiber interface layer rich in LiF on the surface of a copper current collector, characterized in that: include: (1) adding lithium salt to a solvent and stirring and mixing uniformly, and then adding a polymer matrix material and stirring and mixing uniformly to obtain a spinning precursor solution; (2) electrospinning the spinning precursor solution to obtain a nanofiber membrane; and drying the nanofiber membrane by air blast drying and vacuum drying to obtain a nanofiber layer; (3) The nanofiber layer is heat treated and then cooled to room temperature to obtain a LiF-rich nanofiber interface layer.

2. The method for preparing a LiF-rich nanofiber interface layer on the surface of a copper current collector according to claim 1, characterized in that: In step (1), the lithium salt comprises at least one of lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), lithium difluorooxalatoborate, lithium hexafluoroarsenate, and lithium hexafluorophosphate; The mass ratio of lithium salt to polymer matrix material is (1-4):(7-20).

3. The method for preparing a nanofiber interface layer rich in LiF on the surface of a copper current collector according to claim 1, characterized in that: In the step (1), the polymer matrix material includes at least one of polyacrylonitrile, polyvinylidene fluoride, polyethylene oxide and polydimethylsiloxane.

4. The method for preparing a LiF-rich nanofiber interface layer on the surface of a copper current collector according to claim 3, characterized in that: In the step (1), the polymer matrix material includes polyacrylonitrile and polyvinylidene fluoride, and the mass ratio of polyacrylonitrile to polyvinylidene fluoride is (1-3): (0.5-1.5).

5. The method for preparing a LiF-rich nanofiber interface layer on the surface of a copper current collector according to claim 1, characterized in that: In the step (1), the solvent is N, N-dimethylformamide, and the mass ratio of the lithium salt to the volume ratio of the solvent is (0.1-0.4) g: (10-20) mL.

6. The method for preparing a LiF-rich nanofiber interface layer on the surface of a copper current collector according to claim 1, characterized in that: The step (2) comprises the following steps: wrapping a receiving roller of an electrospinning machine with copper foil, taking a spinning precursor solution into a needle tube and connecting the needle, and adjusting the distance between the needle and the receiving roller to 10-15 cm; The spinning time was 8-15 h at a needle advancement rate of 0.02-0.05 mm / min and a spinning voltage of 20-35 kV to prepare a fiber membrane with a thickness of 20-30 μm and a width of 80-120 mm.

7. The method for preparing a nanofiber interface layer rich in LiF on the surface of a copper current collector according to claim 1, characterized in that: In the step (2), the blast drying temperature is 50-80°C and the time is 5-8h; the vacuum drying temperature is 50-80°C and the time is 20-28h.

8. The method for preparing a nanofiber interface layer rich in LiF on the surface of a copper current collector according to claim 1, characterized in that: The heat treatment method in step (3) comprises: placing the nanofiber layer in a Fresnel furnace, heating the temperature to 200-300°C at a heating rate of 1-3°C / min, and naturally cooling the nanofiber layer to room temperature after heat treatment for 1-3 hours.

9. Use of the LiF-rich nanofiber interface layer prepared according to any one of claims 1 to 8 in a battery.